Implementasi Pembelajaran PAI dalam Membentuk Nilai Religius dan Moral Peserta Didik di MAS Plus Al Ulum Medan - Nurhaliza, Siti (Cendekia : Jurnal Pendidikan dan Keagamaan, 2025)
The implementation of Islamic Religious Education (PAI) learning at MAS Plus Al Ulum Medan plays an important role in shaping the religious and moral values of students. PAI learning is systematically designed with a holistic approach, covering cognitive, affective, and psychomotor aspects, thereby instilling spiritual awareness and noble character behavior in students’ daily lives. Through interactive learning methods, the inculcation of Islamic values such as honesty, responsibility, discipline, and respect can be realized concretely. Evaluation results show a significant improvement in students’ religious and moral attitudes, both within the school environment and in the wider community. Therefore, PAI learning at MAS Plus Al Ulum Medan has proven effective in shaping students’ character based on Islamic values.